Recent Progress in Extracellular Vesicle-Based Carriers for Targeted Drug Delivery in Cancer Therapy - Yaqin Tang; Xingyou Liu; Meng Sun; Su Xiong; Nianting Xiao; Jianchao Li; Xiao He; Jing Xie (MDPI AG, 2023)
Extracellular vesicles (EVs) are small, membrane-based vesicles released by cells that play a critical role in various physiological and pathological processes. They act as vehicles for transporting a variety of endogenous cargo molecules, enabling intercellular communication. Due to their natural properties, EVs have emerged as a promising "cell-free therapy" strategy for treating various diseases, including cancer. They serve as excellent carriers for different therapeutics, including nucleic acids, proteins, small molecules, and other nanomaterials. Modifying or engineering EVs can improve the efficacy, targeting, specificity, and biocompatibility of EV-based therapeutics for cancer therapy. In this review, we comprehensively outline the biogenesis, isolation, and methodologies of EVs, as well as their biological functions. We then focus on specific applications of EVs as drug carriers in cancer therapy by citing prominent recent studies. Additionally, we discuss the opportunities and challenges for using EVs as pharmaceutical drug delivery vehicles. Ultimately, we aim to provide theoretical and technical support for the development of EV-based carriers for cancer treatment.